Habitação de interesse social: as moradias anfíbias na Amazônia - Veloso, Bianca Cuvello Romano (Brasil, 2024)
Developed for graduation purposes, in the Architecture and Urban Planning course, this project presents the proposal for an amphibious housing model (floating - stilt), capable of being reproduced on a scale in floodplain or wetland locations. The central idea is to develop a typology that adapts to a broad spectrum of the population. With this, the aim is to provide assistance to those individuals who do not have an absolute income or who fit the standards of urban range 01 (monthly acquisition of up to 02 minimum wages). In this sense, it is emphasized that the production of social housing is diverse and has been produced in Brazil for more than a century with the aim of promoting the provision of housing to those who do not enjoy this right. Likewise, with the development of the program in question, the aim is to develop architectural designs for units with low production costs and high replicability, in order to reduce the housing deficit and promote social inclusion, which would culminate in scaling sustainable urban environment, strengthening the sense of citizenship, in addition to preventing the increase in irregular occupations.